NiSe2 / NC / MXene composite material and preparation method thereof
By preparing NiSe2/NC/MXene composite materials, combining Ti3C2Tx-MXene nanowires and Ni MOF, and selenizing and carbonizing, the problem of low electromagnetic wave absorption performance of MOF-MXene composite materials is solved, and efficient electromagnetic wave absorption and conduction are achieved. Improved performance, meeting the requirements of electromagnetic wave absorption performance and stability.
Patent Information
- Application Number
- CN202411576367.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
The electromagnetic wave absorption performance of existing MOF-MXene composite materials is not high enough, and the conductivity and stability are poor, which limits its application potential.
By preparing NiSe2/NC/MXene composite materials, the combination of Ti3C2Tx-MXene nanowires and Ni MOF is used to increase the specific surface area through alkali etching, and the relative dosage of nickel salts, MOFs and Ti3C2Tx-MXene are regulated to form Evenly dispersed flower-like Ni MOF, selenized and carbonized, enhancing conductivity and structural defects, optimizing impedance matching to improve electromagnetic wave absorption performance.
It realizes excellent electromagnetic wave absorption performance in the range of 2GHz to 18GHz, the effective absorption bandwidth reaches 2.3GHz to 5.68GHz, the minimum reflection loss can reach -33.67dB to -58.46dB, and maintains high conductivity and good thermal stability. .
Smart Images

Figure CN119212361A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic wave absorbing materials, and specifically relates to a NiSe2 / NC / MXene composite material with high electromagnetic wave absorbing ability and a preparation method thereof. Background Art
[0002] With the progress of social civilization, the widespread application of mobile communications, satellite communications, wireless networks and other equipment based on electromagnetic waves has greatly improved human life and services. However, along with these conveniences, the impact of electromagnetic wave radiation on the environment has also received increasing attention. This impact includes interference with the operation of nearby precision equipment and potential harm to the human immune and sensory systems due to long-term exposure to electromagnetic fields. Electromagnetic wave pollution has become the fourth largest environmental problem after noise, air and water pollution.
[0003] Electromagnetic wave absorbing materials can effectively reduce electromagnetic wave pollution. At present, the research on electromagnetic wave absorbing materials mainly focuses on carbon-based electromagnetic wave absorbing materials, MOF-derived electromagnetic wave absorbing materials, and epoxy-based electromagnetic wave absorbing coatings. The attenuation mechanism of electromagnetic waves mainly includes dielectric loss and magnetic loss. However, high density and poor thermal stability are important factors limiting the application of magnetic loss materials.
[0004] Metal organic framework (MOF) is a kind of porous crystalline material formed by self-assembly of metal ions and organic ligands through coordination bonds, which has great prospects in microwave absorption applications. However, MOF has poor conductivity and stability, which limits their potential use. MXene, as a new type of two-dimensional nanomaterial, has high conductivity, large specific surface area, excellent mechanical properties and good thermal stability. Therefore, it can be used in combination with MOF materials, using the advantages of both composition and structure to make the resulting composite material an excellent electromagnetic wave absorption material.
[0005] However, in the current research on MOF-MXene composite materials, there is still the problem that the electromagnetic wave absorption performance is not high enough. Therefore, further improvement research is needed on MOF-MXene composite materials. Summary of the invention
[0006] In view of the problem that the electromagnetic wave absorption performance of MOF-MXene composite materials in the prior art is not high enough, the present invention discloses an optimized method for preparing a composite material of MOF-derived materials and MXene. By increasing the specific surface area of MOF-derived materials and MXene, as well as special selenization and carbonization operations, it is ensured that the final composite material has excellent electromagnetic wave absorption performance and balanced impedance matching.
[0007] A method for preparing a NiSe2 / NC / MXene composite material comprises the following steps:
[0008] S1, preparation of Ti3C2Tx-MXene nanowires;
[0009] Using multilayer Ti3C2Tx-MXene as a raw material and an organic solvent as an intercalation agent, the multilayer Ti3C2Tx-MXene is intercalated to obtain a single-layer Ti3C2Tx-MXene; etching the single-layer Ti3C2Tx-MXene with an alkaline solution to obtain Ti3C2Tx-MXene nanowires;
[0010] S2, preparation of Ni MOF-Ti3C2Tx MXene;
[0011] The nickel salt and the nitrogen-containing ligand of MOF are fully mixed in a mixed solvent under the action of a dispersant, and the Ti3C2Tx-MXene nanowires are immersed therein. After being fully mixed, the obtained mixed liquid is subjected to a microwave reaction, and the reaction product is cooled and separated to obtain a precipitate, and the precipitate is washed and dried to obtain a Ni MOF-Ti3C2Tx MXene with a flower-like morphology;
[0012] S3, preparation of NiSe2 / NC / MXene composites;
[0013] The Ni MOF-Ti3C2Tx MXene and selenium powder were mixed and ground, and the obtained mixture was kept at 300°C to 900°C for 0.5h to 3h under a protective atmosphere to obtain a NiSe2 / NC / MXene composite material.
[0014] In the preparation process of the above-mentioned NiSe2 / NC / MXene composite material, firstly, the use of alkaline solution etching to prepare nanowires can increase the specific surface area of MXene materials and produce more mesoporous structures, so that when the composite material is used, it provides a large number of active sites for the reflection and scattering of electromagnetic waves, thereby improving the electromagnetic wave performance. Secondly, by adjusting the relative amounts of nickel salts, nitrogen-containing ligands of MOF and Ti3C2Tx-MXene nanowires, it is ensured that the formed Ni MOF is uniformly dispersed on the MXene nanowires, and the Ni MOF obtained by in-situ growth has a flower-like morphology. The flower-like morphology of Ni MOF has a large specific surface area and helps to optimize impedance matching, reduce density, and promote multiple reflections and scattering of electromagnetic waves, so that it can effectively absorb and attenuate electromagnetic waves and improve its wave absorption performance. Third, by selenizing and carbonizing Ni MOF respectively, on the one hand, selenizing Ni MOF can form metal selenide, thereby enhancing conductivity, which is beneficial to electromagnetic wave absorption; on the other hand, carbonizing Ni MOF can derive a multi-component structure of Ni component and N-doped C component, which not only creates structural defects, but also the reduced Ni element ensures magnetism, which is beneficial to improve the conductivity of the composite material and improve the electromagnetic wave attenuation ability.
[0015] Generally, in step S1, multilayer Ti3C2Tx-MXene can be purchased through commercial channels or prepared by itself, which is not particularly limited here.
[0016] When it is obtained by self-preparation, hydrofluoric acid is generally used to etch Ti3AlC2 until the Al atomic layer is etched away.
[0017] Specifically, hydrofluoric acid can be prepared by mixing 1g to 5g of metal fluoride with 20mL to 80mL of 7mol / L to 10mol / L inorganic acid; on this basis, 1g to 5g of Ti3AlC2 powder can be etched accordingly. Too little metal fluoride, too little inorganic acid, and too much Ti3AlC2 powder will result in the Al atomic layer in Ti3AlC2 not being completely etched away, making it difficult to form a Ti3C2Tx-MXene with a multilayer structure; while too much metal fluoride, too much inorganic acid, and too little Ti3AlC2 powder will result in over-etching and damage to the Ti3AlC2 structure.
[0018] The above-mentioned metal fluoride can be selected from any one of the fluorides conventionally used to prepare hydrofluoric acid, such as BeF2, LiF, AlF3, ZnF3, PbF2, and the corresponding inorganic acid can be selected from any one of the acids that can be used to prepare hydrofluoric acid, such as hydrochloric acid, nitric acid, sulfuric acid, etc., which will not be repeated here.
[0019] Generally, in step S1, the organic reagent used as the intercalation agent is selected from any one of methanol, ethanol, and isopropanol; of course, it can also be selected from any other organic reagent that can achieve intercalation effect on multilayer Ti3C2Tx-MXene.
[0020] Generally, in step S1, the intercalation treatment is performed by ultrasonically dispersing a mixed solution of an intercalation agent and multilayer Ti3C2Tx-MXene for 0.5 h to 5 h.
[0021] Generally, in step S1, the alkali solution used to etch a single layer of Ti3C2Tx-MXene is selected from any one of sodium hydroxide, potassium hydroxide, barium hydroxide, and calcium hydroxide; of course, it can also be selected from any other alkali solution that can etch the Ti3C2Tx-MXene material to obtain Ti3C2Tx-MXene nanowires, which will not be described one by one here.
[0022] Specifically, in step S2, the dosage ratio of nickel salt, nitrogen-containing ligand of MOF and Ti3C2Tx-MXene nanowire is: at least 0.1mmol nickel salt, at least 0.2mmol nitrogen-containing ligand of MOF and 20mg-100mg Ti3C2Tx-MXene nanowire.
[0023] Fewer nickel salts or nitrogen-containing ligands of MOF will result in the failure to form Ni MOF materials. On this basis, fewer Ti3C2Tx-MXene nanowires will result in lower conductivity and poor node loss performance of the obtained composite material; while more Ti3C2Tx-MXene nanowires can improve conductivity and enhance dielectric loss energy absorption, but will cause poor impedance matching performance, resulting in poor electromagnetic wave absorption performance.
[0024] Preferably, the amount of nickel salt used is 0.1 mmol to 0.6 mmol, and the amount of nitrogen-containing ligands of MOF used is 0.2 mmol to 2.2 mmol, so as to prevent waste caused by excessive nickel salt and nitrogen-containing ligands of MOF.
[0025] Generally, the nickel salt is selected from any one of nickel nitrate, nickel chloride, nickel sulfamate, and nickel sulfate to provide abundant Ni ions for the subsequently generated Ni MOF material; of course, it can also be selected from any other nickel salt that can provide Ni ions for the preparation of Ni MOF, which will not be described one by one here.
[0026] Generally, the nitrogen-containing ligand of MOF is selected from any one of 1,2,4,5-tetra(3-pyrrolyl)benzene, 1,2,4,5-tetrapyrrolylbenzene, and maleic hydrazide to provide atoms coordinated with Ni ions for the subsequently generated Ni MOF material; of course, it can also be selected from any other substance that can provide ligands coordinated with Ni for the preparation of Ni MOF, which will not be described one by one here.
[0027] Based on the above-mentioned amount of Ti3C2Tx-MXene nanowires, 0.1g to 0.8g of dispersant and 5mL to 50mL of mixed solvent are generally used to ensure that the Ni MOF material with a flower-like morphology is evenly dispersed on the Ti3C2Tx-MXene nanowires.
[0028] Preferably, the dispersant is selected from PVPs such as PVPK25, PVPK30, PVPK45, or commercially available mature dispersant products such as polyvinyl pyrrolidone.
[0029] Generally, the mixed solvent is selected from any commercially available conventional solvent medium such as dimethylformamide, anhydrous ethanol, etc. and mixed with water in a volume ratio of 1:1 to 1:6.
[0030] Generally, the immersion time of Ti3C2Tx-MXene nanowires is 3 h to 8 h to balance the adsorption rate and efficiency of Ni ions on Ti3C2TxMxene nanowires.
[0031] Specifically, in step S2, the conditions of the microwave reaction are: temperature of 100°C to 180°C, power of 100W to 250W, and time of 5min to 30min.
[0032] Too low microwave reaction temperature and power, as well as too short microwave reaction time, will result in the failure to generate Ni MOF materials; while too high microwave reaction temperature and power, as well as too long microwave reaction time, will cause the generated Ni MOF materials to present a flaky structure rather than a flower-like morphology, thereby limiting the application effect of the final composite material obtained.
[0033] Specifically, in step S3, Ni MOF-Ti3C2Tx MXene and selenium powder are mixed and ground in a mass ratio of 1:1 to 6:1.
[0034] The purpose of selenization is to convert part of the Ni element into metal selenide. More selenium powder will cause excessive conversion of Ni element into metal selenide, which will cause the conductivity of the obtained composite material to be too strong, which is not conducive to electromagnetic wave absorption; while less selenium powder will result in less metal selenide generated, which will cause the increased conductivity to be too weak, which is also not conducive to electromagnetic wave absorption.
[0035] At the same time, during the insulation process, lower temperature and shorter time will lead to a low degree of carbonization of the obtained composite material, thereby affecting its conductive loss and reducing the electromagnetic wave absorption performance; while higher temperature and longer time will lead to an excessively high degree of carbonization, which is not conducive to the generation of structural defects and ultimately not conducive to the electromagnetic wave absorption performance of the obtained composite material.
[0036] Generally, in step S3, the mixture is heated to 300°C to 900°C and kept warm at a heating rate of 0.2°C / min to 5°C / min to ensure a suitable heating time and a stable microstructure.
[0037] Generally, in step S3, the protective atmosphere may be nitrogen or argon.
[0038] The present invention also provides a NiSe2 / NC / MXene composite material obtained based on the above preparation method, which includes Ti3C2Tx-MXene nanowires and NiSe2 / NC composite materials with flower-like morphology uniformly distributed on the surface thereof.
[0039] The NiSe2 / NC / MXene composite material, firstly, has a nanowire structure in the MXene part, which has a larger specific surface area than the two-dimensional nanostructure in the general MXene part, thus ensuring that the composite material can provide a large number of active sites for the reflection and scattering of electromagnetic waves during application, thereby improving the electromagnetic wave performance. Secondly, Ni MOF, the precursor of the NiSe2 / NC part, has a specific flower-like morphology, which is more conducive to optimizing impedance matching, thereby being able to effectively absorb and attenuate electromagnetic waves and improve its wave absorption performance. Third, NiSe2 / NC is formed by in-situ selenization and carbonization of a Ni MOF precursor with a flower-like morphology. On the one hand, selenization can form metal selenides, thereby enhancing conductivity and facilitating electromagnetic wave absorption. On the other hand, during the carbonization process, the single-component Ni MOF derives a multi-component structure of Ni component and N-doped C component, and the structural defects created are more conducive to improving the conductivity of the composite material, thereby improving the electromagnetic wave attenuation capability. Moreover, the above-mentioned selenization and carbonization processes did not completely destroy the flower-like morphology of its precursor, but only produced a slight collapse, retaining the advantage of a large specific surface area. Maintaining it at a higher temperature for a certain period of time also formed a three-dimensional porous network structure, enhancing the interface polarization and magnetic loss capabilities.
[0040] In addition, the above-mentioned carbonization process converts the single-component Ni MOF into a multi-component system containing a Ni component and an N-doped C component. Firstly, the obtained elemental Ni component has stronger magnetism than other nickel-containing components such as Ni oxide, and thus has better wave absorption. Secondly, the obtained N-doped C component has a stronger conductivity than undoped pure nanoporous carbon and other components, in which N replaces part of C, forming more structural defects.
[0041] The above-mentioned NiSe2 / NC / MXene composite material provided by the present invention has excellent electromagnetic wave absorption performance under predetermined test conditions (mixed evenly with paraffin in a mass ratio of 1:3 to 1:8 and pressed into a coaxial circular ring with an outer diameter of 7.00 mm and an inner diameter of 3.04 mm): under the condition of matching thickness of 1.5 mm to 5.5 mm, within the effective absorption frequency range of 2 GHz to 18.00 GHz, the minimum reflection loss can be as high as -33.67 dB to -58.46 dB, and the effective absorption bandwidth reaches 2.3 GHz to 5.68 GHz, with balanced impedance matching. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a SEM picture of the intermediate Ni MOF-Ti3C2Tx MXene obtained in Example 1 of the present invention;
[0043] Figure 2 is a SEM image of the NiSe2 / NC / MXene composite material obtained in Example 1 of the present invention;
[0044] Figure 3 It is a test graph of the relative complex dielectric real number of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0045] Figure 4 It is a test chart of the relative complex dielectric imaginary number of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0046] Figure 5 This is a test graph of the dielectric loss tangent value of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0047] Figure 6 It is a test graph of the real number of the relative complex magnetic permeability of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0048] Figure 7 It is a test graph of the relative complex permeability imaginary number of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0049] Figure 8 This is a test graph of the magnetic loss tangent value of the NiSe2 / NC / MXene composite material obtained in Examples 1 to 3 of the present invention in the range of 2 GHz to 18 GHz;
[0050] Fig. 9 is a reflection loss diagram of the NiSe2 / NC / MXene composite material obtained in Example 1 of the present invention;
[0051] Fig.10 is a reflection loss diagram of the NiSe2 / NC / MXene composite material obtained in Example 2 of the present invention;
[0052] Fig.11 It is a reflection loss diagram of the NiSe2 / NC / MXene composite material obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0053] For a better understanding of the present invention, the following examples are further illustrative of the present invention and are only used to explain the content of the present invention, but not to limit the present invention. All similar embodiments listed based on the present invention should fall within the scope of protection.
[0054] In the following examples, the multilayer Ti3C2Tx MXene used was prepared in the laboratory according to the following method:
[0055] 3.0 g of BeF2 was slowly added to 50 mL of 9 mol / L hydrochloric acid solution, and stirred in a polytetrafluoroethylene container for 30 min until BeF2 was completely dissolved, and then 3.0 g of Ti3AlC2 powder was slowly added and stirred for 30 min to obtain a reaction mixture; the resulting reaction mixture was stirred at 30°C for 18 h. After stirring, the reaction product was cooled to room temperature and centrifuged; 80 wt% ethanol was used as a washing liquid, mixed with the obtained precipitate in a volume ratio of 3:1 and washed (in a centrifuge at a speed of 5000 rpm) until the pH value was neutral, and then dried at 60°C for 12 h in a drying equipment to obtain multilayer Ti3C2Tx MXene.
[0056] Moreover, based on the above multilayer Ti3C2Tx MXene, Ti3C2Tx MXene nanowires were prepared by the following method:
[0057] The multilayer Ti3C2Tx MXene was placed in a nitrogen environment, methanol was used as an intercalation agent, and ultrasonic dispersion was performed for 1.5 hours for intercalation treatment. The reaction product was centrifuged (at a speed of 4000 rpm), and the supernatant was freeze-dried to obtain a single-layer Ti3C2TxMXene; the single-layer Ti3C2Tx MXene was then etched with a sodium hydroxide solution to obtain Ti3C2Tx MXene nanowires.
[0058] Of course, in the preparation process of the above-mentioned multilayer Ti3C2Tx MXene, the preparation of hydrofluoric acid, the amount of Ti3AlC2 powder, the Al atomic layer etching temperature / time, and the washing conditions and drying conditions can all be appropriately adjusted with reference to the general means in the prior art, and the present invention is not limited thereto.
[0059] At the same time, in the process of preparing multilayer Ti3C2Tx MXene into single-layer Ti3C2Tx MXene, the type of intercalant and the intercalation treatment process can also be appropriately adjusted to obtain single-layer Ti3C2Tx MXene; and, in the process of preparing single-layer Ti3C2Tx MXene into Ti3C2Tx MXene nanowires, the type of etching solution can also be appropriately adjusted to safely etch it into a nanowire structure.
[0060] The differences in the preparation methods of the NiSe2 / NC / MXene composite materials provided in each embodiment will be described in detail below.
[0061] Example 1
[0062] This embodiment provides a method for preparing a NiSe2 / NC / MXene composite material, which also includes the following steps:
[0063] First, 0.3 mmol nickel chloride, 0.5 mmol maleic hydrazide and 0.6 g PVP were added to 45 mL of a mixed solvent (DMF and H2O were mixed in equal volumes) to obtain a mixed solution; then 30 mg Ti3C2Tx MXene nanowires were added and soaked for 5 h, and transferred to 45 mL of a microwave reaction glass, and microwave reaction was carried out at 120 ° C and 150 W for 20 min; the reaction product was cooled to room temperature and centrifuged, and 80 wt% ethanol was used as a washing liquid, mixed with the obtained precipitate at a volume ratio of 2.5:1 and washed (in a centrifuge with a rotation speed of 5000 rpm), and then dried in a vacuum drying oven at 60 ° C for more than 24 h to obtain Ni MOF-Ti3C2TxMXene.
[0064] Then, Ni MOF-Ti3C2Tx MXene and selenium powder were ground and mixed in a mass ratio of 3:1; the obtained mixture was heated to 650°C at a heating rate of 2.5°C / min under nitrogen protection and kept warm for 3 hours. The carbonized product was cooled to room temperature to obtain a black product, thus obtaining a NiSe2 / NC / MXene composite material.
[0065] The Ni MOF-Ti3C2Tx MXene generated in the above preparation process and the final NiSe2 / NC / MXene composite material were tested by SEM, and their SEM images are shown in Figure 1 and Figure 2 shown.
[0066] from Figure 1 It can be seen that the MXene surface is covered with a flower-like film, indicating that Ni MOF with flower-like morphology was successfully generated on the MXene surface by microwave-assisted self-assembly technology. Figure 2 It can be seen that the flower-like structure of NiSe2 / NC / MXene obtained after high-temperature selenization and carbonization has collapsed to a certain extent, but it does not affect the overall structure and can still retain the large specific surface area of the flower-like morphology; and the nanoparticles are evenly and densely distributed on the surface and interlayer of MXene, forming a three-dimensional porous network structure. This structural characteristic enhances the interface polarization and magnetic loss capacity, providing a structural basis for the NiSe2 / NC / MXene composite material to exhibit excellent electromagnetic wave absorption performance.
[0067] Example 2
[0068] This embodiment provides a method for preparing a NiSe2 / NC / MXene composite material, which specifically includes the following steps:
[0069] First, 0.6 mmol nickel nitrate hexahydrate, 2.2 mmol maleic hydrazide and 0.25 g PVP were added to 15 mL of a mixed solvent (DMF and H2O were mixed in equal volumes) to obtain a mixed solution; then 100 mg Ti3C2Tx MXene nanowires were added and soaked for 6 h, and transferred to 30 mL of a microwave reaction glass, and microwave reaction was carried out at 180 ° C and 250 W for 15 min; the reaction product was cooled to room temperature and centrifuged, and 80 wt% ethanol was used as a washing liquid, mixed with the obtained precipitate in a volume ratio of 3:1 and washed (in a centrifuge with a rotation speed of 3500 rpm), and then dried in a vacuum drying oven at 60 ° C for more than 24 h to obtain Ni MOF-Ti3C2TxMXene.
[0070] Then, Ni MOF-Ti3C2Tx MXene and selenium powder were ground and mixed in a mass ratio of 2:1; the obtained mixture was heated to 300°C at a heating rate of 2°C / min under argon protection and kept warm for 3 hours. The carbonized product was cooled to room temperature to obtain a black product, thus obtaining a NiSe2 / NC / MXene composite material.
[0071] Example 3
[0072] This embodiment provides a method for preparing a NiSe2 / NC / MXene composite material, which specifically includes the following steps:
[0073] First, 0.5 mmol nickel chloride, 1.3 mmol maleic hydrazide and 0.6 g PVP were added to 50 mL of a mixed solvent (DMF and H2O were mixed in equal volumes) to obtain a mixed solution; then 70 mg Ti3C2Tx MXene nanowires were added and soaked for 6 h, and transferred to 50 mL of a microwave reaction glass, and microwave reaction was carried out at 100 ° C and 180 W for 30 min; the reaction product was cooled to room temperature and centrifuged, and 80 wt% ethanol was used as a washing liquid, mixed with the obtained precipitate in a volume ratio of 3:1 and washed (in a centrifuge with a rotation speed of 4500 rpm), and then dried in a vacuum drying oven at 60 ° C for more than 24 h to obtain Ni MOF-Ti3C2TxMXene.
[0074] Then, Ni MOF-Ti3C2Tx MXene and selenium powder were ground and mixed in a mass ratio of 5:1; the obtained mixture was heated to 900°C at a heating rate of 3°C / min under nitrogen protection and kept warm for 0.5h. The carbonized product was cooled to room temperature to obtain a black product, thereby obtaining a NiSe2 / NC / MXene composite material.
[0075] Example 4
[0076] This embodiment provides a method for preparing a NiSe2 / NC / MXene composite material, which specifically includes the following steps:
[0077] First, 0.1mmol nickel nitrate hexahydrate, 1.6mmol 1,2,4,5-tetrakis(3-pyrrolyl)benzene and 0.25g PVP were added to 15mL mixed solvent (DMF and H2O were mixed in equal volumes) to obtain a mixed solution; then 20mg Ti3C2Tx MXene nanowires were added and soaked for 6h, and transferred to 30mL microwave reaction glass, and microwave reaction was carried out at 170℃ and 150W for 15min; the reaction product was cooled to room temperature and centrifuged, and 80wt% ethanol was used as a washing liquid, mixed with the obtained precipitate in a volume ratio of 3:1 and washed (in a centrifuge with a rotation speed of 3500rpm), and then dried in a vacuum drying oven at 60℃ for more than 24h to obtain NiMOF-Ti3C2Tx MXene.
[0078] Then, Ni MOF-Ti3C2Tx MXene and selenium powder were ground and mixed in a mass ratio of 1:1; the obtained mixture was heated to 600°C at a heating rate of 2°C / min under argon protection and kept warm for 2 hours. The carbonized product was cooled to room temperature to obtain a black product, thus obtaining a NiSe2 / NC / MXene composite material.
[0079] Example 5
[0080] This embodiment provides a method for preparing a NiSe2 / NC / MXene composite material, which specifically includes the following steps:
[0081] First, 0.5mmol nickel nitrate hexahydrate, 0.2mmol 1,2,4,5-tetrapyrrolylbenzene and 0.25g PVP were added to 15mL mixed solvent (DMF and H2O mixed in equal volumes) to obtain a mixed solution; then 50mg Ti3C2Tx MXene nanowires were added and soaked for 6h, and transferred to 30mL microwave reaction glass, and microwave reaction was carried out at 170℃ and 100W for 5min; the reaction product was cooled to room temperature and centrifuged, and 80wt% ethanol was used as a washing liquid, mixed with the obtained precipitate in a volume ratio of 3:1 and washed (in a centrifuge with a rotation speed of 3500rpm), and then dried in a vacuum drying oven at 60℃ for more than 24h to obtain Ni MOF-Ti3C2Tx MXene.
[0082] Then, Ni MOF-Ti3C2Tx MXene and selenium powder were ground and mixed in a mass ratio of 6:1; the obtained mixture was heated to 700°C at a heating rate of 2°C / min under argon protection and kept warm for 2 hours. The carbonized product was cooled to room temperature to obtain a black product, thus obtaining a NiSe2 / NC / MXene composite material.
[0083] The electromagnetic parameters of the NiSe2 / NC / MXene composite materials obtained in the above embodiments were tested at room temperature using a vector network analyzer sold by Agilent under the trade name PNA Network Analyzer N5224A.
[0084] Specifically, the relative complex dielectric real number, relative complex dielectric imaginary number, dielectric loss tangent value, relative complex magnetic permeability real number, relative complex magnetic permeability imaginary number, and magnetic loss tangent value test graphs of the NiSe2 / NC / MXene composite materials of Examples 1 to 3 in the range of 2 GHz to 18 GHz are shown in order: Figure 3 to Figure 8 shown.
[0085] The NiSe2 / NC / MXene composite material prepared in Example 1 was mixed with paraffin wax in a mass ratio of 1:4 and heated to 80°C to completely melt the paraffin wax and fully mix with the NiSe2 / NC / MXene composite material. The liquid mixture was poured into a mold and cooled to room temperature, and then pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm to obtain the first test sample.
[0086] The NiSe2 / NC / MXene composite material prepared in Example 2 was mixed with paraffin in a mass ratio of 1:5, and the rest was referred to the above method of Example 1 to obtain a second test sample.
[0087] The NiSe2 / NC / MXene composite material prepared in Example 3 was mixed with paraffin in a mass ratio of 1:8, and the rest was referred to the above method of Example 1 to obtain a third test sample.
[0088] Based on the electromagnetic parameters obtained from the above tests, according to the method described in document 1 (Luo Kong, et al. Flexible CNTs / CNFWPU aerogel for smart electromagnetic wave absorbing with tuning effective absorption bandwidth[J]. Carbon, 2023, 207: 13-22), the reflection loss diagrams of each NiSe2 / NC / MXene composite material were obtained by transmission line theory calculation, as shown in the figure. Figures 9 to 11 shown.
[0089] from Fig. 9 It can be seen that the best wave absorbing performance of the NiSe2 / NC / MXene composite material prepared in the above Example 1 is under the conditions of matching thickness 5mm and frequency 4.92GHz, its minimum reflection loss is -33.67dB, and the effective absorption bandwidth is 2.3GHz in the frequency range of 2GHz to 18GHz.
[0090] from Fig.10 It can be seen that the best wave absorbing performance of the NiSe2 / NC / MXene composite material prepared in the above Example 2 is under the conditions of matching thickness 1.5mm and frequency 17.34GHz, its minimum reflection loss is -58.46dB, and the effective absorption bandwidth is 5.68GHz in the frequency range of 2GHz to 18GHz.
[0091] from Fig.11 It can be seen that the best wave absorbing performance of the NiSe2 / NC / MXene composite material prepared in the above Example 3 is under the conditions of matching thickness of 3.5 mm and frequency of 6.73 GHz, its minimum reflection loss is -39.69 dB, and the effective absorption bandwidth is 3.73 GHz in the frequency range of 2 GHz to 18 GHz.
[0092] Using the same testing method as mentioned above, the best wave absorption performance of the NiSe2 / NC / MXene composite material prepared in Example 4 is obtained under the conditions of matching thickness 2mm and frequency 10.92GHz, with a minimum reflection loss of -50.79dB and an effective absorption bandwidth of 5.02GHz in the frequency range of 2GHz to 18GHz.
[0093] Using the same testing method as mentioned above, the best wave absorption performance of the NiSe2 / NC / MXene composite material prepared in Example 5 is obtained under the conditions of matching thickness of 2.5 mm and frequency of 13.68 GHz, with a minimum reflection loss of -42.69 dB and an effective absorption bandwidth of 4.65 GHz in the frequency range of 2 GHz to 18 GHz.
[0094] The NiSe2 / NC / MXene composite materials provided in the above embodiments have excellent minimum reflection loss and effective absorption bandwidth data, ensuring balanced impedance matching.
[0095] In order to verify the necessity of the nanowire structure, flower-like morphology, selenization and carbonization in the preparation methods of the above embodiments, several comparative experiments were conducted.
[0096] Comparative Example 1
[0097] This comparative example is intended to demonstrate the necessity of the nanowire structure.
[0098] The difference between this comparative example and Example 1 is that a single-layer Ti3C2Tx MXene is used instead of Ti3C2Tx MXene nanowires to prepare Ni MOF-Ti3C2Tx MXene; the rest is as shown in Example 1 to obtain a first comparative composite material.
[0099] Comparative Example 2
[0100] This comparative example aims to demonstrate the necessity of the flower-like morphology of Ni MOF.
[0101] The difference between this comparative example and Example 2 is that, in the preparation process of Ni MOF-Ti3C2Tx MXene, the conditions of the microwave reaction are: microwave treatment for 30 min at a temperature of 190°C and a power of 220 W; the rest is as shown in Example 2 to obtain a second comparative composite material.
[0102] Comparative Example 3
[0103] This comparative example is intended to demonstrate the necessity of selenization and carbonization.
[0104] The difference between this comparative example and Example 3 is that the prepared Ni MOF-Ti3C2Tx MXene is used as the third comparative composite material; that is, selenization and carbonization treatment are avoided.
[0105] Comparative Example 4
[0106] This comparative example is intended to demonstrate the necessity of selenization and carbonization.
[0107] The difference between this comparative example and Example 4 is that before Ni MOF-Ti3C2Tx MXene is kept warm, it is not mixed and ground with selenium powder, but directly heated and kept warm using the same heating process; the rest is as shown in Example 4 to obtain a fourth comparative composite material.
[0108] The same test method was used to measure the electromagnetic parameters of each comparative composite material, and the reflection loss was calculated accordingly. The results are as follows:
[0109] The best wave absorbing performance of the NiSe2 / NC / MXene composite material prepared in Comparative Example 1 is that under the conditions of matching thickness of 5 mm and frequency of 3.67 GHz, its minimum reflection loss is -20.15 dB, and the effective absorption bandwidth is 1.3 GHz in the frequency range of 2 GHz to 18 GHz.
[0110] The best wave absorption performance of the NiSe2 / NC / MXene composite material prepared in Comparative Example 2 is that under the conditions of matching thickness of 1.5 mm and frequency of 9.38 GHz, its minimum reflection loss is -32.67 dB, and the effective absorption bandwidth is 2.2 GHz in the frequency range of 2 GHz to 18 GHz.
[0111] The best wave absorption performance of the NiSe2 / NC / MXene composite material prepared in Comparative Example 3 is that under the conditions of matching thickness of 3.5 mm and frequency of 16.21 GHz, its minimum reflection loss is -23.18 dB, and the effective absorption bandwidth is 1.6 GHz in the frequency range of 2 GHz to 18 GHz.
[0112] The best wave absorption performance of the NiSe2 / NC / MXene composite material prepared in Comparative Example 4 is that under the conditions of matching thickness 2mm and frequency 6.72GHz, its minimum reflection loss is -30.27dB, and the effective absorption bandwidth is 2.05GHz in the frequency range of 2GHz to 18GHz.
[0113] By comparing the performance of the composite materials obtained in the above-mentioned Example 1 and Comparative Example 1, it can be seen that the minimum reflection loss and effective absorption bandwidth data of the composite material finally obtained by using a single-layer Ti3C2Tx MXene to replace the Ti3C2Tx MXene nanowire to prepare Ni MOF-Ti3C2Tx MXene in Comparative Example 1 are significantly worse; this is because, compared with a single-layer Ti3C2Tx MXene, Ti3C2Tx MXene nanowires can better increase the specific surface area, produce more mesopores, and provide a large number of active sites for the reflection and scattering of electromagnetic waves, thereby improving the electromagnetic wave performance.
[0114] By comparing the performance of the composite materials obtained in the above-mentioned Example 2 and Comparative Example 2, it can be seen that in Comparative Example 2, a higher microwave temperature is used to prepare the Ni MOF material. Even if the microwave reaction power is appropriately reduced, it can be observed that the Ni MOF is irregularly flaky after the preparation is completed, and no flower-like morphology is formed. The minimum reflection loss of the composite material finally obtained can only reach -32.67dB, which is significantly worse than -58.46dB in Example 2, and the effective absorption bandwidth data is also worse. This is because the Ni MOF with a flower-like morphology helps to optimize impedance matching, reduce density, and promote multiple reflections and scattering of electromagnetic waves, so that it can effectively absorb and attenuate electromagnetic waves, thereby improving its wave absorption performance.
[0115] By comparing the performance of the composite materials obtained in the above-mentioned Example 3 and Comparative Example 3, it can be seen that when the Ni MOF-Ti3C2Tx MXene without selenization and carbonization is used as a composite material, it can only achieve a minimum reflection loss of -23.18dB, which is much lower than the minimum reflection loss of the corresponding NiSe2 / NC / MXene composite material obtained after selenization and carbonization, and the effective absorption bandwidth data is also worse, so its electromagnetic wave absorption performance is not good. This is because, on the one hand, the metal selenide formed after selenization is more conducive to the absorption of electromagnetic waves than metals, and the carbonization treatment can derive Ni components and N-doped C components from Ni MOF, transforming the single-component structure into a multi-component structure, while creating structural defects, thereby improving the conductivity of the composite material and improving the electromagnetic wave attenuation ability.
[0116] By comparing the performance of the composite materials obtained in the above-mentioned Example 4 and Comparative Example 4, it can be seen that when the Ni MOF-Ti3C2Tx MXene (referred to as NiSe2 MOF-Ti3C2Tx MXene) which is only selenized but not carbonized is used as the composite material, it can only achieve a minimum reflection loss of -30.27 dB, which is much lower than -50.79 dB in Example 4, and the effective absorption bandwidth data is also worse, so its electromagnetic wave absorption performance is not good. This is because carbonization is conducive to the single-component Ni MOF to derive the Ni component and the N-doped C component to form a multi-component structure, while creating structural defects, thereby improving the conductivity of the composite material and improving the electromagnetic wave attenuation ability.
[0117] The embodiments used above are only for illustrating and explaining the contents of the present invention, and do not constitute any special limitation to the present invention. Any form of modification made without departing from the basic concept of the present invention, as well as the obvious modifications derived therefrom, shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a NiSe2 / NC / MXene composite material, characterized in that: Includes steps: S1, preparation of Ti3C2Tx-MXene nanowires; Using multilayer Ti3C2Tx-MXene as a raw material and an organic solvent as an intercalation agent, the multilayer Ti3C2Tx-MXene is intercalated to obtain a single-layer Ti3C2Tx-MXene; then etching the single-layer Ti3C2Tx-MXene with an alkaline solution to obtain the Ti3C2Tx-MXene nanowire; S2, preparation of Ni MOF-Ti3C2Tx MXene; The nickel salt and the nitrogen-containing ligand of the MOF are fully mixed in a mixed solvent under the action of a dispersant, and the Ti3C2Tx-MXene nanowires are immersed therein; After being fully mixed, the obtained mixed liquid is subjected to microwave reaction at a temperature of 100° C. to 180° C. and a power of 100 W to 250 W for 5 min to 30 min, the reaction product is cooled and separated to obtain a precipitate, and the precipitate is washed and dried to obtain Ni MOF-Ti3C2Tx MXene having a flower-like morphology; The nickel salt, the nitrogen-containing ligand of MOF and the Ti3C2Tx-MXene nanowires are used in a ratio of at least 0.1 mmol of the nickel salt, at least 0.2 mmol of the nitrogen-containing ligand of MOF and 20 mg to 100 mg of the Ti3C2Tx-MXene nanowires. S3, preparation of NiSe2 / NC / MXene composites; The Ni MOF-Ti3C2Tx MXene and selenium powder are mixed and ground in a mass ratio of 1:1 to 6:1, and the obtained mixture is kept at 300° C. to 900° C. for 0.5 h to 3 h under a protective atmosphere to obtain the NiSe2 / NC / MXene composite material.
2. The preparation method according to claim 1, characterized in that: In step S2, the nickel salt is used in an amount of 0.1 mmol to 0.6 mmol, and the nitrogen-containing ligand of the MOF is used in an amount of 0.2 mmol to 2.2 mmol.
3. The preparation method according to any one of claims 1 or 2, characterized in that: The nickel salt is selected from any one of nickel nitrate, nickel chloride, nickel sulfamate, and nickel sulfate; the nitrogen-containing ligand of the MOF is selected from any one of 1,2,4,5-tetrakis(3-pyrrolyl)benzene, 1,2,4,5-tetrapyrrolylbenzene, and maleic hydrazide.
4. The preparation method according to claim 3, characterized in that: In step S2, the amount of the dispersant is 0.1 g to 0.8 g, and the amount of the mixed solvent is 5 mL to 50 mL.
5. The preparation method according to claim 4, characterized in that: The dispersant is PVP or polyvinyl pyrrolidone; the mixed solvent is a mixture of any one of dimethylformamide and anhydrous ethanol and water in a volume ratio of 1:1 to 1:
6.
6. The preparation method according to claim 1, characterized in that: In step S1, the organic reagent used as an intercalation agent is selected from any one of methanol, ethanol, and isopropanol; the alkaline solution used to etch the single-layer Ti3C2Tx-MXene is selected from any one of sodium hydroxide, potassium hydroxide, barium hydroxide, and calcium hydroxide.
7. The preparation method according to claim 1, characterized in that: In step S3, the mixture is heated to 300°C to 900°C at a heating rate of 0.2°C / min to 5°C / min and kept warm.
8. A NiSe2 / NC / MXene composite material, characterized in that: The invention comprises Ti3C2Tx-MXene nanowires and a NiSe2 / NC composite material with a flower-like morphology uniformly distributed on the surface of the Ti3C2Tx-MXene nanowires.
